Pembuatan Perahu Sande’ (Studi Mitologi Masyarakat Pamboang Kabupaten Majene) (Equilibrium: Jurnal Pendidikan, 2019)
The main problems in this study are (1) To analyze how the stages of ritual procession of public trust in Sande boat making ', (2) To analyze what the symbolic message is contained in the ritual procession of public confidence in the making of Sande' s boat. This research was conducted in Pamboang District, Bonde Village, Majene Regency. This type of research is descriptive with qualitative approach. Primary data obtained through in-depth interviews to the parties that have been determined by using purposive sampling techniques, as well as direct observation in the field. Secondary data is obtained from data collection through documents and literature related to the research topic. The results of this study indicate that the ritual procession that accompanies Sande boat making is seen in three major stages ie before boatbuilding, boat making process and after boatbuilding. The meaning contained in the implementation of the ritual is the hope that always be given salvation by Allah SWT in using the boat. In addition, the ritual also intends to invoke the abundant sustenance of the process of going to sea later.Keywords: Mythology, Sande 'Boat, Society.